Mathematical models of solar chimneys with a phase change material for ventilation of buildings: A review using global energy balance. (1st March 2019) - Vargas-López, R.; Xamán, J.; Hernández-Pérez, I.; Arce, J.; Zavala-Guillén, I.; Jiménez, M.J.; Heras, M.R.
Abstract: The solar chimney is one concept currently explored by scientists and designers for reducing heat gain and inducing natural cooling in both commercial and residential buildings. Solar chimneys can be installed on the building walls and roofs. In this sense, a significant amount of research work has been done on solar chimney since the 1990s. This paper presents an overview of transient mathematical models for solar chimneys with/without a phase change material. The review focuses on the Global Energy Balance (GEB) models and a short description of the main works is reported. The analysis of the literature on the solar chimney modeling using GEBhighlights that the transient mathematical model are scarce, from the authors' knowledge, there are only 24 published works and only six studies incorporated a phase change material (PCM) in a solar chimney. Five steady mathematical models available in the literature were analyzed, as well as the advantages and disadvantages of each model. Based on the analysis, it is concluded that the model - III and model - V are more appropriate to model the transient state with respect to the remaining models, and therefore the unsteady mathematical model –III and model - V were developed and shown. These models are highly recommended to be implemented as a solar chimney model in a Building Energy Simulation (BES) program. Finally, we propose a new transient mathematical model for a double-channel solar chimney, which incorporated a phase change material (PCM). This new mathematical model allows building designers and engineers to predict the potential benefit that a solar chimney with PCMmay have for ventilation. Therefore, this paper would provide a valuable reference for further research into the field of solar chimneys with a PCMand its applications.